Answer:
See explanation
Step-by-step explanation:
![(x^2+9x+10)(x-2)= \\\\x^3-2x^2+9x^2-18x+10x-20= \\\\x^3+7x^2-8x-20](https://tex.z-dn.net/?f=%28x%5E2%2B9x%2B10%29%28x-2%29%3D%20%5C%5C%5C%5Cx%5E3-2x%5E2%2B9x%5E2-18x%2B10x-20%3D%20%5C%5C%5C%5Cx%5E3%2B7x%5E2-8x-20)
Jimmy is incorrect.
Using long division, you can find that the real answer.
First, subtract
from the original expression, leaving you with
.
Next, subtract
from the expression, leaving you with
. Finally, subtract
from the expression, leaving you with a remainder of 0. This means that the real quotient is
. Hope this helps!
Answer: 7
7 is the middle number when the number are out from least to greatest. Hope that helps!!
Answer:
No
Step-by-step explanation:
The Triangle Inequality Theorem states that the sum of any 2 sides of a triangle must be greater than the measure of the third side.
We see that: 4.1 + 1.3 < 8.4
=> Can't form a triangle from 4.1 cm, 8.1 cm and 1.3 cm
Answer:
Step-by-step explanation:
If two chords intersect inside a circle, then
DE * BE =AE * CE
10*x = 8*6
10x = 48
x = 48/10
x = 4.8
Answer:
About 1.26%
Step-by-step explanation:
Divide 15,750 by 12,500 to find your answer.
Hope this helped!